2013
DOI: 10.5539/jfr.v2n3p22
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Irradiation for Dry-Roasting of Hazelnuts and Evaluation of Microwave Treatment on Hazelnuts Peeling and Fatty Acid Oxidation

Abstract: European hazelnut is an important nut crop in Italy, where about 121,750 tons of in-shell nuts are produced every year. Roasting is the most important practice for hazelnut preservation and commonly is carried out in commercial electrical ovens at 120-160°C for 10-20 min. This needful practice is time and energy expensive, so the development of new processing methods is required to reduce processing costs and to obtain top quality roasted nuts. The aim of this study was to develop a simple microwave treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Roasting involves a number of physico-chemical changes including dehydration and chemical reactions (Ciarmiello et al 2013). According to results, fatty acid composition and phenolic compounds were affected by conventional oven and microwave heating.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roasting involves a number of physico-chemical changes including dehydration and chemical reactions (Ciarmiello et al 2013). According to results, fatty acid composition and phenolic compounds were affected by conventional oven and microwave heating.…”
Section: Resultsmentioning
confidence: 99%
“…Turkey, especially coast of the Black Sea region, is the most important producer of hazelnut, contributing about 70.3% of the total world production (Alasalvar et al 2010;Jakopic et al 2011). The quality and fatty acid composition of hazelnut can be affected by climatic conditions, variety, location and cultural practices (Alasalvar et al 2010;Ciarmiello et al 2013). Hazelnut are rich source of essentials minerals, sterols, fatty acids, free phenolic acids, organic acids and phenolic compounds (gallic acid etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hot air roasting is a convective heat transfer process, and the temperature rises as a function of heat transfer. As the nut temperature approaches 120 °C, the rate of temperature increase slows and the moisture evaporation accelerates [ 27 ]. In the present study, static hot air treatment generally induced a higher detoxification with increasing exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…In comments, the evaluators described microwave-roasted hazelnuts as "typical for good-quality chocolates with nuts". Ciarmiello et al studies compared microwave-roasted hazelnuts treated with exposures times of 240, 300, 360, 4 indicated that the best taste score was recorded with 450 s and 600 s microwave treatment [28].…”
Section: Hazelnutsmentioning
confidence: 99%